Agroturismo y oferta turística en la Parroquia de Columbe, Cantón Colta - Caiza Paucar, Luis Anibal (2022)
The following research aimed to analyze the relationship between agritourism and the tourist offer in the parish of Columbe, canton, the methodology used is descriptive, field, and documentary, the study design is cross-sectional, not experimental, qualitative and quantitative. Questionnaires were applied on the Likert scale, for the independent variable agrotourism for the reason of the Covid-19 pandemic, members of the Columbe parish GAD were taken as part of the sample, components of economic activity, agrotourism activities, recreational activities were evaluated. To the dependent variable study, tourist offer due to the Covid-19 pandemic, the community councils of the parish were taken as a sample, focusing on the aspects: goods and services, resources and infrastructure, with the data obtained used some statistical methods such as Cronbach's Alpha to verify the reliability of the instruments, as well as the SPSS v23 statistic that allowed the analysis and interpretation of the results, from which the general and specific hypotheses could be verified using the statistical tool of chi square which it was evidenced that agrotourism and tourist offer have no influence on the Columbe Parish. In view of the investigation results, the proposal was to design an agritourism product called "Mishky Murukuna Ñan"